PERAN NATIONAL FEDERATION OF FEMALE COMMUNITIES OF KYRGYZSTAN (NFFCK) DALAM MELAWAN TRADISI ALA KACHUU DI KIRGISTAN - Rahmad, Aulia; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to explain the cooperation between non-governmental organizations (NGOs), non-state actors, and intergovernmental organizations (IGOs), organizations formed by states. The case study in this research is the collaboration between National Federation of Female Communities of Kyrgyzstan (NFFCK) and the United Nations Trust Fund. NFFCK is an NGO engaged in the campaign  for the right of Kyrgyz women to end kachuu-style practices, a series of acts of forced kidnappingwomen with the aim of marrying them.UN Trust Fund is a program in the form of funding from the United Nations provided to NGOs with the aim of ending crimes against women in their countries. Through grants provided by the United Nations, NFFCK started its advocacy from January 2015 to December 2016 to play its role in fighting the practice of kidnapping brides in Kyrgyzstan. This study uses pluralism perspective which argues  the important role of non-state actors in the dynamics of  international relations. This descriptive qualitative research uses data collection techniques through document analysis or secondary data analysis, such as books, journals, official publications, reports, and websites. The theory of the relationship between NGOs and IGOs to explain how the cooperation that exists in realizing the interests of both. With assistance provided by the UN Trust Fund, NFFCK is carrying out a number of activities aimed at increasing understanding of ala kachuu. The program run by NFFCK  has  produced  positive  results, many participants  have benefited from joining the program. The programs offered are also  considered  to  be in accordance with the conditions of the Kyrgyz society, so they can be well accepted. This is evidenced by various surveys conducted by the UN Trust Fund, in which the NFFCK program has reached more than 12,000 participants with a percentage of 93% who have benefited. However, this achievement will not continue due to the duration of cooperation between NFFCK and the United Nations which only lasted 2 years. So it takes a sustainable role from the Kyrgyz government to be able to tackle the phenomenon of bride kidnapping in this country. Keywords: Kyrgyzstan, NGOs,  IGOs, NFFCK, United Nations, Ala Kachuu, and Bride Kidnapping